Exploring public preferences and demand for ovarian cancer screening: a discrete choice experiment - Hall, Rebekah; Spencer, Anne E.; Lloyd, Abigail; Hamilton, Willie; Medina-Lara, Antonieta (Frontiers in Oncology, 2025)
IntroductionRoutine population-level screening may in the future reduce the high mortality rates associated with late-stage ovarian cancer diagnosis. However, the voluntary nature of screening means that understanding the public’s acceptability of the benefits, harms and likely uptake of any potential screening programme is crucial to implementation.ObjectiveTo measure public preferences towards the benefits and harms of a potential screening programme and to predict uptake.MethodsAn online Discrete Choice Experiment was completed by 250 women 40-80 years old in England and Wales. Subjects were asked 12 questions where they were asked to choose between two hypothetical screening tests described in terms of four attributes; ovarian cancer deaths, false-positive, false-negative and overdiagnosis rates, and no screening. Responses were analysed using mixed logit regression.ResultsIn total, 250 women completed the survey. Ovarian cancer deaths (0.42, [95% CI: 0.40 – 0.44]) was the most important attribute overall, followed by the rate of false positive results (0.30, [95% CI: 0.30-0.30]). However, there were high levels of heterogeneity with individuals exhibiting low levels of worry about ovarian cancer (OR=1.76 [95% CI: 1.17–2.69]), low perceived risk of ovarian cancer (OR=1.44 [95% 1.03–2.03]) or risk-averse individuals (OR=1.46 [95% CI: 1.05–2.04]) significantly more likely to opt for the no screening alternative. Oppositely, individuals who regularly participate in cervical screening (OR=0.63 [0.47–0.90]) were less likely to opt for no screening. Overall, results indicated participants would be willing to accept 2.59 (95% CI: 1.82 – 3.36) false-negative results, 205 (95% CI: 161 – 248) false-positive results and 2.35 (95% CI: 1.76-2.94) per 10,000 people screened to avoid 1 ovarian cancer-related death. Uptake analysis confirmed a high willingness to undergo screening across varying levels of benefits and harms.ConclusionsCurrently ovarian cancer screening is not recommended as available screening methods do not offer benefits in terms of mortality reduction. The results of this study demonstrate a high demand for ovarian cancer screening and a willingness to trade between the benefits and risks of a potential test. Results of this study provide a useful resource for assessing the acceptability of future screening modalities which may become available.